Monogenic early-onset lymphoproliferation and autoimmunity: the natural history of stat3 gof syndrome - ÖZEN, AHMET OĞUZHAN (My University, 2022)
Background: In 2014, germline signal transducer and activator of transcription (STAT) 3 gain-of-function (GOF) mutations were first described to cause a novel multisystem disease of early-onset lymphoproliferation and autoimmunity. Objective: This pivotal cohort study defines the scope, natural history, treatment, and overall survival of a large global cohort of patients with pathogenic STAT3 GOF variants. Methods: We identified 191 patients from 33 countries with 72 unique mutations. Inclusion criteria included symptoms of immune dysregulation and a biochemically confirmed germline heterozygous GOF variant in STAT3. 1 Results: Overall survival was 88%, median age at onset of symptoms was 2.3 years, and median age at diagnosis was 12 years. Immune dysregulatory features were present in all patients: lymphoproliferation was the most common manifestation (73%); increased frequencies of double-negative (CD42CD82) T cells were found in 83% of patients tested. Autoimmune cytopenias were the second most common clinical manifestation (67%), followed by growth delay, enteropathy, skin disease, pulmonary disease, endocrinopathy, arthritis, autoimmune hepatitis, neurologic disease, vasculopathy, renal disease, and malignancy. Infections were reported in 72% of the cohort. A cellular and humoral immunodeficiency was observed in 37% and 51% of patients, respectively. Clinical symptoms dramatically improved in patients treated with JAK inhibitors, while a variety of other immunomodulatory treatment modalities were less efficacious. Thus far, 23 patients have undergone bone marrow transplantation, with a 62% survival rate. Conclusion: : STAT3 GOF patients present with a wide array of immune-mediated disease including lymphoproliferation, autoimmune cytopenias, and multisystem autoimmunity. Patient care tends to be siloed, without a clear treatment strategy. Thus, early identification and prompt treatment implementation are lifesaving for STAT3 GOF syndrome. (J Allergy Clin Immunol 2022
Keywords: STAT3; gain of function; lymphoproliferation; cytopenia; autoimmunity; immune dysregulation; immunodeficiency; precision medicine